Nanomedicines - Muhammad Akhyar Farrukh (IntechOpen, 2019)
Nanomedicine is the application of nanotechnology in medicines at an atomic, molecular, and supramolecular level. Nanomedicine covers a wide range of topics from the development of nanomaterials for use in medicines to the synthesis of nanomedicines with their multiple applications. The major focus of the book is on developments in nanomedicines and their effectiveness compared to conventional drugs. Some drugs are administered twice daily for days and weeks. However, the frequency of administration and dosage of drugs can be reduced to increase patient compliance when prepared at the nanoscale level with polymers, etc. This book contains five chapters from leading scientists working in the area of nanomedicines. Particular topics that are highlighted are exosomes, nanoantimicrobial solutions, transethosomes, nanoethosomes, nanoparticles, multifunctional drugs, and natural dietary products.
English
Keywords: Biomedical Engineering; Physical Sciences; Engineering and Technology; Technology